Investigation of VLF Electromagnetic Undersea Positioning System Using Receiving Antenna Array in a Simulation - Shinnosuke Sakaya; Masaharu Takahashi (IEEE Access, 2025)
In this paper, we propose a 3D undersea positioning system using VLF electromagnetic waves as a system to support divers’ activities in seawater and show results of a basic study for the proposed system in electromagnetic field simulations. Assuming that a transmitting antenna is attached to a diver, the antenna’s position in seawater is estimated using the Received Signal Strength (RSS [dB]) of multiple receiving antennas placed near the sea surface. To assist in the installation and retrieval of the proposed system, we propose a receiving antenna array that integrates twelve dipole antennas into a single receiver. Furthermore, we also propose a position estimation algorithm optimized for the proposed receiver. In the proposed algorithm, Support Vector Regression (SVR) was utilized to estimate the distance between the transmitting antenna and the receiver from the RSS. We confirmed that position estimation using the receiver was possible within a circle with an approximately 12 m radius centered on the receiver, demonstrating the viability of our proposed system for implementation.